Fundamentals of computation theory : 19th International Symposium, FCT 2013, Liverpool, UK, August 19-21, 2013. Proceedings - Wolter, Frank; Gasieniec, Leszek (Lecture Notes in Computer Science, 2013)
This book constitutes the refereed proceedings of the 19th International Symposium on Fundamentals of Computation Theory, FCT 2013, held in Liverpool, UK, in August 2013. The 29 papers (26 full papers and 3 invited papers) were carefully reviewed and selected from 58 submissions. The papers cover the following topics: algorithms, formal methods, and emerging fields.